2022
DOI: 10.1038/s41467-022-31522-x
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Induced Civil Conflict Among the Ancient Maya

Abstract: The influence of climate change on civil conflict and societal instability in the premodern world is a subject of much debate, in part because of the limited temporal or disciplinary scope of case studies. We present a transdisciplinary case study that combines archeological, historical, and paleoclimate datasets to explore the dynamic, shifting relationships among climate change, civil conflict, and political collapse at Mayapan, the largest Postclassic Maya capital of the Yucatán Peninsula in the thirteenth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Strategies for settlement occupation and drivers of settlement abandonment (or the changing settlement pattern) vary in different geographic locations and societies throughout time and are hence controlled by environmental and societal factors (Butzer, 2005(Butzer, , 2012Boyer et al, 2006;McLeman, 2011). Environmental triggers encompass various types of natural hazards such as RCC events, (flash) floods, earthquakes, landslides, volcanic eruptions, and the ensuing geomorphodynamics (soil erosion and mass movements) (Black et al, 2011;Dusar et al, 2011;Palmisano et al, 2021;Zhang et al, 2021;Kennett et al, 2022). This last factor might be important in the Tekkedere catchment.…”
Section: Mid-to Late Holocene Geomorphodynamicsmentioning
confidence: 99%
“…Strategies for settlement occupation and drivers of settlement abandonment (or the changing settlement pattern) vary in different geographic locations and societies throughout time and are hence controlled by environmental and societal factors (Butzer, 2005(Butzer, , 2012Boyer et al, 2006;McLeman, 2011). Environmental triggers encompass various types of natural hazards such as RCC events, (flash) floods, earthquakes, landslides, volcanic eruptions, and the ensuing geomorphodynamics (soil erosion and mass movements) (Black et al, 2011;Dusar et al, 2011;Palmisano et al, 2021;Zhang et al, 2021;Kennett et al, 2022). This last factor might be important in the Tekkedere catchment.…”
Section: Mid-to Late Holocene Geomorphodynamicsmentioning
confidence: 99%
“…For example, spatial reconstruction of the hydroclimate variability over the Northern Hemisphere showed that a larger percentage of land area was under relatively wetter conditions in the warm period, and under drier conditions in the cold period. However, some studies found that during the Medieval Climate Anomaly (MCA, AD 950–1250), hydrological anomalies resulted in drier conditions over most parts of the globe (Diaz et al, 2011); in particular, prolonged droughts (roughly AD 750–1050) occurred over the western United States and northern Mexico and drought‐induced civil war conflict that triggered the collapse of the Mayan civilization (Aimers & Hodell, 2011; Kennett et al, 2022). In addition, Wilhelm et al (2022) found a warming of 0.5–1.2°C led to a 25%–50% decrease in the frequency of large floods in the European Alps.…”
Section: Introductionmentioning
confidence: 99%
“… Integration of elements indicating: (i) examples of approaches to determine ancient environmental change and societal complexity; (ii) a regional/local ancient collapse described by an example from Mayapan, the largest Postclassic Mayan city [ 20 ]; and (iii) the modern potential global collapses described by Kemp et al. [ 1 ].…”
mentioning
confidence: 99%
“…It also highlights the relevance of ancient technologies and management strategies to mitigate the consequences of the complexity of climate change (e.g. Refs [ 20–25 ]).…”
mentioning
confidence: 99%
See 1 more Smart Citation